Penitential Manuscripts and the Teaching of Penance in Carolingian Europe - Leontidou, Eleni (Studies in church history, 2019)
This article discusses the educational value of penitential literature in Carolingian Francia. In particular, it looks at manuscripts which were not simple penitential handbooks but were compiled as educational tools for priests. Apart from penitential works, these manuscripts included monastic rules, moral and ascetic works providing moral instruction, and, in some cases, school texts and glossaries.